2022
DOI: 10.1038/s41598-022-11218-4
|View full text |Cite
|
Sign up to set email alerts
|

Invasions of an obligate asexual daphnid species support the nearly neutral theory

Abstract: To verify the “nearly neutral theory (NNT),” the ratio of nonsynonymous to synonymous substitutions (dN/dS) was compared among populations of different species. To determine the validity of NNT, however, populations that are genetically isolated from each other but share the same selection agents and differ in size should be compared. Genetically different lineages of obligate asexual Daphnia pulex invading Japan from North America are an ideal example as they satisfy these prerequisites. Therefore, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…The following sequences were used to infer the tree: Daphnia pulex LC705055.1, D. pulex LC632389.1 (Ohtsuki et al. 2022 ), D. pulex AF117817.1 (Crease 1999 ), D. mitsukuri MW699926.1, D. galeata LC152879.1 (Tokishita et al. 2017 ), D. laevis MK059395.1 (Martins Ribeiro et al.…”
Section: Resultsmentioning
confidence: 99%
“…The following sequences were used to infer the tree: Daphnia pulex LC705055.1, D. pulex LC632389.1 (Ohtsuki et al. 2022 ), D. pulex AF117817.1 (Crease 1999 ), D. mitsukuri MW699926.1, D. galeata LC152879.1 (Tokishita et al. 2017 ), D. laevis MK059395.1 (Martins Ribeiro et al.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in each lineage, we used a majority of the genotypes distributed in Japan. Moreover, the genotypes used in this study were the same as those used by Ohtsuki et al (2022), who examined the number of nonsynonymous and synonymous mutations (dN/dS ratio) within these lineages. According to that study, the dN/dS ratio within the JPN1 lineage was lower than that of the JPN2 lineage, suggesting that the former lineage was more efficiently subjected to purification selections (Ohta, 1973(Ohta, , 1992Houle et al, 1996;Bataillon, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ohtsuki et al (2022) found that the base substitution rate estimated from whole-genome sequences was larger among the genotypes of the JPN1 lineage when compared with those of the JPN2 lineage, indicating that the divergent age of the JPN1 lineage is older than that of the JPN2. Moreover, the dN/dS ratio was significantly lower within the JPN1 than within the JPN2 lineage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Daphnia species, D. cf. pulex sensu Hebert (1995), often referred to as panarctic D. pulex (Colbourne et al, 1998), has obligate asexual lineages (Innes & Hebert, 1988;Ohtsuki et al, 2022;Paland et al, 2005). These lineages were originally found in North America but have expanded their range to other continents and continental islands, including Japan (Ma et al, 2019;So et al, 2015;Ye et al, 2021).…”
Section: Introductionmentioning
confidence: 99%